Traumatic Cardiac Injury: Ventricular Perforation Caught on CT - Behrad Golshani; Paul Dong; Scott Evans (Case Reports in Radiology)
Myocardial rupture is a rare imaging diagnosis given its clinical severity and high mortality. Early findings should be promptly communicated to the trauma service to ensure immediate intervention. We present a rare case of blowout perforation of the right ventricle which was prospectively diagnosed on computed tomography (CT) leading to emergent operative repair. The patient subsequently survived and was discharged after a lengthy hospital course.